Factors Affecting the Performance of Employees: Analysis in Muhammadiyah Sukabumi University - Iqbal Noor; Alhidayatullah; Muhammad Abdul Aziz; Muhammad Khairul Amal (PT FORMOSA CENDEKIA GLOBAL, 2023)
Leadership and organizational culture are important factors determining employee performance and ability to adapt to environmental changes. Phenomena that happened at the University of Muhammadiyah Sukabumi is employee work that is still not optimal. The problem studied from this study is how the description of the leadership and organizational culture of the University of Muhammadiyah Sukabumi. This study aims to find out and describe the influence of leadership and organizational culture on the work of employees of the University of Muhammadiyah Sukabumi, either simultan or partially. The data from this study are all employees of the University of Muhammadiyah Sukabumi which total of 250 people. The sampling technique in this study uses census study population techniques so that the entire population is used as a sample. The questionnaire method of data collection is employed, and multiple regression analysis with simultaneous testing and partial test hypothesis testing was the method of analysis used in this investigation. Leadership and organizational culture have a beneficial impact on employee performance, according to the partial variable results of the regression analysis. Leadership, which affects employee performance by 69.3%, is the dominant independent variable. The magnitude of the influence of the independent variable on the bound is 75.0% while the rest is as much as 25. 0% is influenced by other factors that are not studied such as salary and performance support